Rob Johnson, Janne Haaland Matlary (ed.), The United Kingdom’s Defence after Brexit. Britain’s alliances, coalitions, and partnership, Wydawnictwo Palgrave Macmillan, Cham 2019, ss. 261 - Kamil Pietrasik (Facta Simonidis)
Recenzja: Rob Johnson, Janne Haaland Matlary (ed.), The United Kingdom’s Defence after Brexit. Britain’s alliances, coalitions, and partnership, Wydawnictwo Palgrave Macmillan, Cham 2019, ss. 261